Platelet Indices as Quility markers For Remission in patients with Leukemia - Suleimman Al-Sweedan; Ismail Matalka (Mediterranean Journal of Hematology and Infectious Diseases)
The purpose of this study was to investigate whether platelet indices [mean platelet volume (MPV) and platelet distribution width (PDW)] could serve as surrogate marker for follow-up in patients with leukemia. Blood samples were obtained from 48 patients with leukemia at diagnosis before chemotherapy and at the time of remission (mean age: 17.92 years; 24 males and 24 females). We measured the blood platelet indices using an automated counter. MPV was higher at the time of remission, but it was not statistically significant. However, PDW was significantly lower (P<0.001) at the time of remission. There was no significant difference in the MPV or PDW in patients with acute lymphoblastic leukemia versus acute myeloblastic, males versus females or in patients on chemotherapy versus no chemotherapy at the time of remission. In conclusion, we found no significant difference in the MPV between the two groups. PDW proposed as indicators of certain pathologic conditions and it seems possible to use PDW as surrogate markers foe follow up in patients with leukemia. However, platelet indices (MPV and PDW) cannot be used as indicator to discriminate between the subtypes of leukemia. The potential role of platelet indices in leukemia remains to be investigated by a multi institutional level to verify the possible clinical significance of this finding.